THE PROACTIVE ENGAGEMENT OF OXFAM INTERNATIONAL AS INTERNATIONAL NON- GOVERNMENTAL ORGANIZATION (INGO) TO SOLVE SOMALIA FOOD INSECURITY PROBLEM - Hendra Manurung (Universitas Jenderal Ahmad Yani, 2017)
Somalia experienced 19 (nineteen) years for food crisis problem since 1992, and reached its peak in 2011. The crisis worsened by long standing conflict in the country combined with climate change, with the result that United Nations declared Somalia to be famine in 2011. The food crisis has driven world’s attention, especially non-governmental organizations concern on humanitarian issues, such as Oxfam International. In 1992, Oxfam International engaged to overcome food crisis and continue sustainable participation in addressing food crisis in 2011. Oxfam International cooperate with the local communities in Somalia by building water sanitation, providing clean water, delivering assistances such as foods, medicines, and also providing cash money. Oxfam International also supports and trains local people, especially farmers in agriculture, so they can produce food. By trained local farmers, it can help produce enough food to feed the population and reduce the possibility of famine in Somalia. The objective of this research is to explain the Oxfam International leading role in doing proactive involvement for humanitarian aids in Africa. The analysis is done based on the role of international non-governmental organization to handling the issue of food security in Somalia. To conclude, Oxfam International has shown meaningful efforts to give long- term impact on solving food insecurity problem in Somalia.